Yttrium-90 selective internal radiation therapy on liver cancer: the past, the present, and the future - Jingqin MA; Linhong ZHANG; Minjie YANG; Jiabin CAI; Ying FANG; Rong LIU; Xudong QU; Lingxiao LIU; Zhiping YAN (Zhongguo Linchuang Yixue)
Yttrium-90 selective internal radiation therapy (90Y-SIRT) is a treatment technique that delivers radioactive microspheres precisely to the arterial vascular bed of neoplasms, utilizing beta radiation to administer a high local dose of radiation to the neoplasm tissues. This technology has demonstrated significant efficacy in patients with unresectable pirmary liver cancers and liver metastases. This article systematically reviews the development history and clinical application status of 90Y-SIRT in the treatment of liver cancer, and looks forward to future development directions.